Assimilative and Accommodative Coping and Older People's Leisure Activities. (3rd June 2019) - Tourunen, Anu; Siltanen, Sini; Portegijs, Erja; Eronen, Johanna; Rantanen, Taina; Saajanaho, Milla
Objectives: Assimilative and accommodative coping strategies have hardly been studied in relation to leisure activities in old age. We investigated whether tenacious goal pursuit (TGP) and flexible goal adjustment (FGA) influence the association between physical performance and participation in leisure activities.Methods: A cross-sectional analysis was conducted among 187 community-dwelling people aged 79 to 93 years. TGP, FGA, and leisure activity participation were asked with questionnaires. Physical performance was assessed with the Short Physical Performance Battery (SPPB).Results: TGP moderated the relationship between physical performance and leisure activity participation. Despite low physical performance, people with high TGP had close to mean level of leisure activity participation, whereas low TGP was associated with very little activity. Most notably, people without high TGP had fewer outdoor activities and group activities outside home. Similar effects were not found for FGA.Discussion: Persistency, rather than flexibility, in goal pursuit appears to help older people be active in their leisure time.